Does Foreign Aid Improve Governance? - Matthias Busse; Steffen Groening (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This paper analyses the impact of aid flows on governance. Using an instrumental variable approach and a large country sample, we find that aid has a negative rather than a positive influence on governance. This outcome is robust to various model specifications.
Keywords: C33; F35; O11; O43; 330; Official Development Assistance; Governance